Survival outcomes of marijuana users in p16 positive oropharynx cancer patients - Han Zhang; Michael Xie; Marc Levin; Stuart D. Archibald; B. Stanley Jackson; J. E. M. Young; Michael K. Gupta (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Oropharynx squamous cell carcinoma (OPSCC) has become the predominant subsite for head and neck mucosal cancers (HNC) due to the rise of human papillomavirus (HPV) related disease. Previous studies have suggested an association between marijuana use and HPV-related OPSCC. Despite this, no study has examined the potential relationship between marijuana use and survival in this subset of patients. Objective To examine the survival outcomes of HPV-related OPSCC patients in marijuana users. Methods Patients who were marijuana users were identified from a prospectively collected database of HNC patients from January 2011 to 2015. A physical review of clinic records was undertaken to extract relevant patient, tumor, treatment, follow-up, as well as survival data. Patients greater than 17 years of age with pathologically proven p16 positive OPSCC were included. They were then case-matched in a 1-to-1 basis to patients who were non-marijuana users based on age, gender, and cTNM staging. Results Forty-Seven patients met inclusion criteria within each group. Univariate logistic regression analysis showed that age, gender, and cT-Stage were predictive of disease recurrence within both groups (p < 0.05). However, cN-stage, treatment modality, tumor subsite, tobacco use, and tobacco dose were not (p > 0.05). There was no statistically significant difference between marijuana and non-marijuana user groups in 5-year (p = 0.400) overall survival, disease-specific (p = 0.993), disease-free (p = 0.404), and metastasis-free survival (p = 0.384). Conclusions No survival difference is found between HPV-related OPSCC marijuana users and non-users. This finding has implications for both de-escalation regimes and the use of cannabis as a therapeutic agent.